Predictive risk factors for one-year mortality in idiopathic inflammatory myopathy patients with interstitial lung disease: A retrospective, single-center cohort study - Minna Jiang,; Xiaohong Wen,; Sisi Xia,; Yiqun Guo,; Yu Bai, (Archives of Rheumatology, 2024)
Objectives: This study aimed to analyze the risk factors for mortality of idiopathic inflammatory myopathy (IIM) patients admitted with interstitial lung disease (ILD) to guide rapid and accurate judgment of clinical prognosis. Patients and methods: This retrospective, single-center cohort study was conducted with 135 participants (37 males, 98 females; mean age: 54.8±11.1 years; range, 24 to 85 years) between June 1, 2016, and June 30, 2021. The participants were categorized into the survival group (n=111) and nonsurvivors (n=24) according to whether they survived during the one-year follow-up. The independent risk factors for mortality in one year after discharge were analyzed. Receiver operating characteristic curve analysis was used to determine the accuracy of oxygenation index at baseline combined with pulmonary infection (PI) at follow-up to indicate death in IIM-ILD patients. Results: Compared to the survival group, nonsurvivors were older (p=0.006) and had a higher proportion of anti-MDA5 (melanoma differentiation-associated protein 5) positivity (p<0.001). The ILD duration was shorter (p=0.006), the oxygenation index was lower (p<0.001), and the intensive care unit occupancy rate (p<0.001) and ventilator utilization rate (p<0.001) were elevated in nonsurvivors compared to the survival group. Oxygenation index at baseline (odds ratio [OR]=1.021, 95% confidence interval [CI]: 1.001-1.023, p=0.040) and PI (clinical judgment) at follow-up (OR=16.471, 95% CI: 1.565-173.365, p=0.020) were found as independent risk factors for death in the year after discharge in IIM inpatients with ILD. An oxygenation index ≤279 mmHg at baseline combined with PI at follow-up exhibited a promising predictive value for all-cause death in IIM-ILD patients within one year. Conclusion: Oxygenation index at baseline and PI during follow-up were independent risk factors for death of IIM-ILD patients within one year after discharge. Patients with an oxygenation index ≤279 mmHg at baseline had an increased risk of death once they developed PI during the one-year follow-up.